Soils, their formation, properties, composition, and relations to climate and plant growth in the humid and arid regions - Hilgard, Eugene W. (Eugene Woldemar), 1833-1916 (Salt Lake City, UT : Project Gutenberg, 2024)
"Soils: Their Formation, Properties, Composition, and Relations to Climate and Plant Growth" by E. W. Hilgard is a scientific publication written in the early 20th century. The book serves as both a text and reference on soil science and aims to provide insights into the formation, characteristics, and significance of soils in agricultural practices across different climates, particularly focusing on arid and humid regions. Likely intended for students and agricultural professionals, it combines detailed scientific observations with practical applications. The opening of the book begins with a preface that outlines the author's motivation for creating a comprehensive resource on soil studies, particularly in the context of the author's experiences with newly settled agricultural regions. It highlights the importance of understanding soil science for the cultivation of crops and the general welfare of mankind, emphasizing the relationships between soil properties and plant growth. The introduction defines key concepts related to soil, including its formation from rocks through physical and chemical processes, and introduces the structured chapters which will delve into various aspects of soil formation, composition, and implications for agriculture. (This is an automatically generated summary.)
Release date is 2024-07-05
Charlene Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/Canadian Libraries)
Keywords: Soils